A Report on Human Skeletal Remains from the Mausoleum of Emir Qurqumas in Cairo Investigated in 1976-1981 - Dzierżykray-Rogalski, Tadeusz; Promińska, Elżbieta (Anthropological Review, 1983)
The architectural complex of Qurqumas located in the eastern part of the “town of dead” at Cairo, has been constructed at the turn of 15th century (construction completed in 1507). From a number of crypts have been hitherto obtained 7 skeletons of infants (O years of life), 9 of children aged 3 to 14 years, 2 of juveniles (18-20 yrs), 11 of adult males and 24 of adult females. All persons’ buried in crypts apparently belonged ‚to the ruling Glass having thus the best for heir times living conditions. This fact is reflected in their life span. For adult males average age at death was 525 years, for adult females — 55.4. These averages are higher than for people buried at the Medieval cemetery of Kom-El-Dikka in Alexandria and similar to observed among present day Egyptian urban population. The report is a preliminary one, work upon skeletal material from Emir Qurqumas’ mausoleum will continue.